2014
DOI: 10.1080/13662716.2015.1012825
|View full text |Cite
|
Sign up to set email alerts
|

Openness and Innovation Performance: Are Small Firms Different?

Abstract: We explore whether and how the benefits of openness in innovation are different for small plants (less than 50 employees) compared to medium and large plants. Using panel data from Irish manufacturing we find that the contribution of the 'breadth' of openness (i.e. the variety of plants' innovation linkages) on innovation performance is stronger for small plants than for larger plants. Both small and larger plants face diminishing returns as the breadth of openness increases, but small plants experience negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 47 publications
5
85
1
Order By: Relevance
“…While research in the early 2000's was criticised for focusing on large technology-based firms and not accounting for differences in the innovation process between large and smaller firms (West and Gallagher 2006), more recent research has sought to address this imbalance (Van de Vrande et al 2009;Lee, Park, Yoon and Park 2010;Vahter et al 2014;Colombo, Piva and Rossi-Lamastra 2014) 2 . As a result, we now have a much better understanding of the antecedents of OI in SMEs (Schroll and Mild 2011), how OI enhances SME internal capabilities (Huizingh, 2011), the type of external partners and nature of relationships formed by SMEs for research exploration and innovation exploitation (Lee et al 2010), and the performance benefits of adopting OI (Colombo, Laursen, Magnusson and Rossi-Lamastra 2012;Colombo et al 2014).…”
Section: Openness and Open Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…While research in the early 2000's was criticised for focusing on large technology-based firms and not accounting for differences in the innovation process between large and smaller firms (West and Gallagher 2006), more recent research has sought to address this imbalance (Van de Vrande et al 2009;Lee, Park, Yoon and Park 2010;Vahter et al 2014;Colombo, Piva and Rossi-Lamastra 2014) 2 . As a result, we now have a much better understanding of the antecedents of OI in SMEs (Schroll and Mild 2011), how OI enhances SME internal capabilities (Huizingh, 2011), the type of external partners and nature of relationships formed by SMEs for research exploration and innovation exploitation (Lee et al 2010), and the performance benefits of adopting OI (Colombo, Laursen, Magnusson and Rossi-Lamastra 2012;Colombo et al 2014).…”
Section: Openness and Open Innovationmentioning
confidence: 99%
“…And, where firms do adopt OI, the degree of openness -measured, for example, by the number of types of innovation partners with which firms are working -often remains well below the optimal level (e.g. Vahter et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they emphasized the value of open innovative research for SMEs [10]. Vahter et al (2012) found that small businesses was stronger than large enterprises in terms of opening breadth impact on innovation performance, and small businesses could significant benefit from open innovation strategy, but choosing the right open innovation model was an significant issue to be studied compared with large enterprises by using the 1994-2008 panel data of Irish manufacturing firms [11]. Mei Qiang & Dai Yuanyuan (2013) found enterprise independent innovation and open innovation may work through mutual collaboration in innovation performance by high-tech SMEs cases and cross-case comparative analysis [12].…”
Section: The Impact Of Open Innovation For Smes Performancementioning
confidence: 99%
“…Laursen and Salter (2006: 131) found that "those who search widely and deeply -tend to be more innova!ve". However, several more methodologically rigorous studies have found a nega!ve rela!onship between too much openness and innova!on performance (Enkel et al, 2009;Laursen and Salter, 2004;Vahter et al, 2012). A Norwegian inves!ga!on found that there are different strategies of openness, concluding that firms should strive to maintain "organiza!onal contexts" and build competences rather than blindly follow a general collabora!ve orienta!on .…”
Section: Hypothesismentioning
confidence: 99%